ESENSI GURU DAN PENTINGNYA KEBERADAAN GURU DALAM SISTEM PEMBELAJARAN VEDA: PERSPEKTIF TEOLOGI PENDIDIKAN - I Ketut Donder; Prasanthy Devi Maheswari (Veda Jyotih: Jurnal Agama dan Sains, 2024)
Guru is word which is used in Sanskrit language, the root of the Guru wordis, Gu means who one has free from material attachment, and Ru means whoone can help other to cross of the ocean sin. So, the word Guru is not directlymeaning a teacher, Guru is one has a spiritual qualification. Guru whenteaching, he known deeply his student till their inner. So, nickname of Guruis the special title of a teacher who has beyond than the general teachers.Because of the very special qualification of the Guru, therefore Guru has verycentral in the Vedic education system. All about that, is very clear if we readthe Upanisad, and directly find many descriptions about the significant of theGuru.This research paper based on the literature study, therefore the all datacollected from literatures. The research method used is qualitative method,and the analysis data method use qualitative analysis method which completedwith interpretation method. And then used theory of meaning to analysis ofthe research problems.The result research found that everyone who want become the best qualificationin the Vedic knowledge, he/she should seek the true Guru. Because the Vedicknowledge is likes unlimited wide ocean or is likes the very big forest, thereforewho one wants to learn Vedic knowledge without lead by the true Guru, thenthe learning result has not perfect. Many aphorisms in Vedic knowledge isnot easy to understand, for the example, in Vedic teaching 'sky' is calledfather, and earth is called mother, cow also called as mother. In short, Vedicknowledge mostly used symbol to sign of the Supreme, therefore the existenceof the true Guru is the core of learning Vedic process.